Food and agribusiness yearbook '97. (University of Asia and the Pacific, 1997)
Purpose: To "provide comprehensive and relevant information necessary for the sustained growth of this significant sector and an extensive agribusiness-oriented directory for buyers, entrepreneurs, farmers, and businessmen to help them make the most of their enterprise.